Anti-aging Activity, In Silico Modeling and Molecular Docking from Sonneratia Caseolaris - Syamsul, Eka Siswanto; Umar, Salman; Wahyuni, Fatma Sri; Martien, Ronny; Hamidi, Dachriyanus (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Anti-aging agents contribute to the prevention and control of skin photoaging. Antioxidant containing cosmetic has anti-aging therapy that can inhibit free radical formation. Sonneratia caseolaris leaf extract has robust antioxidant activity. AIM: This study aimed to determine the anti-aging activity in-silico and in-vitro. METHODS: In vitro antioxidant potential was evaluated by 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2-Azino-bis-(3-ethylbenzothiazoline-6-sulfonate) cation (ABTS+) radical scavenging and FRAP. Investigation of in-silico docking activity was done for ROS (3ZBF), collagenase (966C), hyaluronidase (1FCV) receptors. Metabolomics analysis were conducted through HR-LCMS on the extract Sonneratia caseolaris. To explore the use value of antiaging, we analyzed the molecular docking of metabolites profiling Sonneratia caseolaris. RESULTS: The result of metabolite profiling on the HR-LCMS from Sonneratia caseolaris extract are Luteolin, Betaine, and Choline. Molecular docking involves the exploration of protein or nucleotide, 3D structural modeling, and binding energy calculation. DPPH method showed IC50 28.214±0.809 ppm. The ABTS method showed IC50 1.528±0.042 ppm and FRAP is 345,125±4,196 mM/g sample. The compound luteolin had the Lowest binding energy scores with most of the target proteins: ROS (-8,3), collagenase (-11), and hyaluronidase (-6,8), according to molecular docking results. CONCLUSION: It concluded that the study indicates extract Sonneratia caseolaris has the potential to be developed as a new drug for antiaging.